THE EFFECT OF TAX PLANNING AND POLITICAL COSTS ON PROFIT MANAGEMENT WITH PROFITABILITY AS MODERATING VARIABLES - Sri Nofita Salama; Fransiskus Randa; Suwandy Ng (SIMAK, 2022)
This study aims to investigate whether the tax planning and political cost hasan influence on earning management, and whether profitability moderates theinfluence of tax planning and political cost on earning management. The populationon this study is all the companies listed in Indonesia Stock Exchange on 2017-2019 period. The number of sample are 56 companies each year determined usingthe purposive sampling method. Collecting data used documentation of financialstatement from Indonesia Stock Exchange. Data were analyzed using SPSS 21.The result of this study shows that tax planning has a significant and positiveimpact on earning management, in contrast, the political cost has no impact onearning management. Profitability moderates the relation of tax planning andearning management but doesn’t moderates the impact of political cost andearning management.